2018
DOI: 10.5051/jpis.2018.48.4.236
|View full text |Cite
|
Sign up to set email alerts
|

Alveolar ridge preservation with a collagen material: a randomized controlled trial

Abstract: PurposeResorption of the alveolar bone is an unavoidable consequence of tooth extraction when appropriate alveolar ridge preservation (ARP) measures are not taken. The objective of this trial was to test the hypothesis that dimensional changes in the alveolar bone after tooth extraction would be reduced by inserting an equine collagen membrane and a collagen cone to fill and seal the alveolus (as ARP), in comparison to extraction with untreated alveoli.MethodsIn this randomized clinical trial, 31 patients were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 23 publications
(38 reference statements)
0
9
0
Order By: Relevance
“…However, with the methods employed in the present study, it can be concluded that the combination material has no proven influence or clinical relevance on the formation of new bone, neither can a possible influence be disproved. However, the clinical evaluation according to ARP showed a significant volume preservation in the buccal aspect of the alveolus with the collagen material used (Schnutenhaus, Doering, Dreyhaupt, Rudolph, & Luthardt, ). A potential advantage of delayed implant placement after a healing period of more than 3 months when performing ARP needs to be assessed in further investigations.…”
Section: Discussionmentioning
confidence: 99%
“…However, with the methods employed in the present study, it can be concluded that the combination material has no proven influence or clinical relevance on the formation of new bone, neither can a possible influence be disproved. However, the clinical evaluation according to ARP showed a significant volume preservation in the buccal aspect of the alveolus with the collagen material used (Schnutenhaus, Doering, Dreyhaupt, Rudolph, & Luthardt, ). A potential advantage of delayed implant placement after a healing period of more than 3 months when performing ARP needs to be assessed in further investigations.…”
Section: Discussionmentioning
confidence: 99%
“…As regards dental care, equine tendon collagen products effectively reduce bone resorption after teeth removal and induce bone regeneration with a bone structure similar to natural [ 167 ]. To this, a high number of equine tendon collagen products (t-Barrier ® , Biocollagen ® , Xenomatrix ® , Bio-gen ® , Bioart ® , Kollagen ® , Parasorb ® ) are actually clinically used for the treatment of periodontitis [ 121 , 126 ], alveolar ridge preservation after tooth extraction [ 77 , 168 ], edentulism [ 125 ], maxillary sinus lift [ 119 ], intraoral donor sites regeneration [ 164 ], root perforation [ 163 ] and radicular cyst [ 120 ].…”
Section: Currently Approved Equine Collagen-based Devicesmentioning
confidence: 99%
“…In periodontitis, collagen sheets are successfully applied on the bone root to increase the amount of periodontal connective tissue attachment, with new cementum and new bone formation, in order to decrease the pocket depth and restore the gingival recession [ 121 , 126 ]. After tooth extraction, bone resorption is avoided by improving alveolar bone regeneration by mean of an equine tendon collagen sponge that, by the formation on a stable blood clot, gives a natural support for osteoid differentiation and the subsequent calcification [ 119 , 168 ], besides guides epithelial and connective cells important for the post-extraction soft-tissues healing [ 125 ]. The enhancement of the bone strength in sockets or bone gaps by collagen may be due to its intrinsic angioconductivity and osteoconductivity [ 77 , 119 ].…”
Section: Currently Approved Equine Collagen-based Devicesmentioning
confidence: 99%
“…Furthermore, the storage of the collagen had no negative effects on the histological level. On the other hand, significant preservation of the alveolar ridge was demonstrated in the area of the maxillary anterior teeth [ 24 ].…”
Section: Introductionmentioning
confidence: 99%